Sosialisasi Pencegahan dan Penyuluhan Penyakit Asam Urat di Dusun Kradenan, Desa Srimulyo, Kecamatan piyungan, Kabupaten Bantul - Larasati, Dwi; Arviani, Arviani (Universitas Negeri Gorontalo, 2024)
Gout is a condition resulting from elevated levels of uric acid in the blood, primarily affecting the elderly and causing joint pain, which can significantly disrupt daily activities. There is a widespread lack of understanding regarding the distinction between gout-induced pain and pain caused by other conditions. This community service initiative aims to enhance public awareness concerning the typical symptoms of gout, strategies for managing acute attacks, and preventive measures to mitigate the likelihood of future episodes. The program commences with the assessment of participants' uric acid levels, followed by an informative session delivered by PowerPoint presentations. Subsequently, the material presentation transitions into interactive discussions and a question-and-answer segment. This activity proceeded smoothly as planned and was perceived positively by the participants. Positive initiatives should be developed to help reduce gout sufferers and maintain a healthy diet.